Metabolic Rate Allometry in Intertidal Mussels Across Environmental Gradients: The Role of Coastal Carbonate System Parameters in Mediating the Effects of Latitude and Temperature - Garcia-Herrera, C (Elsevier Ltd, 2022)
We assess the role of direct and indirect effects of coastal environmental drivers (including the parameters of the carbonate system) on energy expenditure (MR) and body mass (M) of the intertidal mussel, Perumytilus purpuratus, across 10 populations distributed over 2800 km along the Southern Eastern Pacific (SEP) coast. We find biogeographic and local variation in carbonate system variables mediates the effects of latitude and temperature on metabolic rate allometry along the SEP coast. Also, the fitted Piecewise Structural Equation models (PSEM) have greater predictive ability (conditional R2 = 0.95) relative to the allometric scaling model (R2 = 0.35). The largest standardized coefficients for MR and M were determined by the influence of temperature and latitude, followed by pCO2, pH, total alkalinity, and salinity. Thus, physiological diversity of P. purpuratus along the SEP coast emerges as the result of direct and indirect effects of biogeographic and local environmental variables. © 2022 Elsevier Ltd